2015
DOI: 10.1007/s10826-015-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Health Problems and Service Use Among First-Time Juvenile Offenders

Abstract: It is known that youth engaged in the juvenile justice system show high rates of psychiatric disorders. However, little is known about the course of those disorders over time, or about mental health service use on the part of children and families during justice system involvement. Boys and girls recruited from their first contact with juvenile court (n=75), at a mean age of 13.6 years, completed three waves of interviews, each consisting of a structured clinical interview and questionnaires regarding service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 28 publications
2
40
0
5
Order By: Relevance
“…Regular forensic settings act mainly as controlling environments aimed primarily at security [36], not assessing nor addressing properly the mental health intervention needs of young offenders [17, 26]. As some authors emphasized [17], forensic mental health services that simultaneously assess and meet mental health and security needs of delinquent youth are essential, particularly for those with severe forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular forensic settings act mainly as controlling environments aimed primarily at security [36], not assessing nor addressing properly the mental health intervention needs of young offenders [17, 26]. As some authors emphasized [17], forensic mental health services that simultaneously assess and meet mental health and security needs of delinquent youth are essential, particularly for those with severe forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Burke et al [26] found that relatively few youth (approximately 20 %) were in contact with mental health services. This is especially relevant, since it is well established that antisocial individuals tend to have a better response to treatment in early developmental stages, such as adolescence [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Oppositional defiant disorder (ODD) is defined by the ICD (WHO, ) and Diagnostic and Statistical Manual of Mental Disorders ( DSM ; American Psychiatric Association, ) as a recurrent pattern of defiant, disobedient, and hostile behavior beginning in childhood or adolescence. Together with attention deficit hyperactivity disorder (ADHD) and conduct disorder, ODD is one of the leading reasons for referral and continued involvement in youth services (Burke, Mulvey, & Schubert, ). The worldwide lifetime prevalence rate of ODD is 10% and among those with ODD, the majority meet criteria for at least one other concurrent psychiatric diagnosis, including both internalizing (depression, anxiety) and externalizing (ADHD, conduct disorder, substance use) problems (Nock, Kazdin, Hiripi, & Kessler, ).…”
mentioning
confidence: 99%
“…More than 50,000 youth categorized as juvenile offenders were detained in private or public facilities in 2013 and 2014 in the United States (Hockenberry, Wachter, & Sladky, ; Office of Juvenile Justice and Delinquency Prevention, 2017). A majority of these youth have mental health diagnoses or needs (Burke, Mulvey, & Schubert, ; Lyons, Baerger, Quigley, Elrich, & Griffin, ; Shuflet & Cocozza, ), and correctional facilities provide treatment and rehabilitative services for youth and their families. For provision of these services, a necessary first step includes identification of mental health needs through evaluation.…”
mentioning
confidence: 99%